Komunikasi Dakwah Rasulullah: Telaah Surat-surat Rasulullah - Ramdani, Fauziah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2019)
This study aimed to describe the background of letter’s used as a medium for da'wah by the Prophet Muhammad and the form of the Prophet Muhammad’s letters for da'wah conveyed to some rulers. To achieve this, the method employed was historical research. This type of research was qualitative using historical approach while the research specification was descriptive. The result shows that there were several reasons behind the sending of letters as a medium for da’wah by Prophet Muhammad to the rulers. First, sociologically it was due to the treaty of Hudaibiyah, then the successfulness of Prophet Muhammad in establishing people power in Medina, and the conflict between Emperor Heraclius and Khosrow Abrawiz, two rulers of two empires (those were Eastern Rome and Persian) which were the most powerful kingdoms in the earth. Second, politically, the letter of Prophet Muhammad had political nuance, that was to declare himself being the ruler of Medina. Third, theologically, it was the universality of Muhammad’s prophetic mission as the leader of the mankind, and the crisis of faith experienced by Negus (Ruler of Abyssinia) and Muqawqis (Ruler of Egypt). To sum up, the form of Prophet’ letters sent to the rulers were awesome, it is proven that the letters of the Prophet which were written by his secretary Zaid son of Thabit were always preceded with Basmalah, while the letters were addressed to disbelieving people. This study has implication on research or study on the importance of letter as a medium for da’wah of the Prophet which can possibly be a method of initiating and or developing da’wah in the present time.